Relationship Between Body Mass Index With Menstrual Pain Scale At Senior High School 9 Padang - Riska Rusydi; Samnil Astuti Fitri; Fitratur Rahmah Agustina (Journal of Nutrition Science, 2023)
There are many changes that occur in adolescence. One of the most prominent is the occurrence of menstruation in adolescents. Menstruation is generally accompanied by pain in the lower abdomen and hips. At Senior High School (SHS) 9 Padang, it was found that 76.4% of young women experienced menstrual pain. The scale of menstrual pain varies in intensity for each person. One thing that influences menstrual pain is Body Mass Index (BMI). Therefore, it necessary to analyze there was a relationship between BMI and the menstrual pain scale. This research is a quantitative study with a cross sectional design. The population was all female adolescents at SHS 9 Padang with a total sample 79 people taken by multistage random sampling. Data analysis used the chi square test using SPSS. The results showed that 71.4% of adolecents with an underweight BMI had a moderate menstrual pain scale and 37.1% an overweight BMI had a heavy menstrual pain scale. There is a relationship between Body Mass Index (BMI) and the menstrual pain scale in adolescents at Senior High School 9 Padang (p=0.00).